SEMIOTIKA PADA MICROLIBRARY BIMA BANDUNG - Noorzanah, R Aj. Dewi Sekar; Laksemi, Sangayu Ketut; Hutama, Krishna (Universitas Trisakti, 2022)
Abstract Semiotics at the Bima Bandung Microlibrary. The study of semiotics in building has not been done much. Therefore, I conduct a study of the message behind architectural design in the context of semiotic theory by taking the case of the Bima Bandung microlibrary. The purpose of this study is to understand the denotative and connotative messages in the Bima microlibrary. The study refers to the case study method of qualitative research. In the microlibrary Bima conveys a message of 1)war against low literacy levels, 2) is an example of improving public spaces, 3) giving messages of environmentally conscious design, 4)the use of used plastic buckets is arranged to form the word